Interactive Duel Service Game Training to Improve Badminton Backhand Serve at SMPN Gollek School No 34 Selayar Islands - Suwardi, Suwardi; Badaru, Benny; Hasanuddin, M. Imran; Fahrizal, Fahrizal; Badar, Muhammad; Mulyadi, Mulyadi (Universitas Pejuang Republik Indonesia, 2025)
Interactive serve duel game training in badminton at SMPN Gollek No 34 Kepulauan SelayarSelayar was designed to develop students' basic technical competencies in mastering backhand serve and improve accuracy and confidence in playing badminton. This program provides opportunities for students to understand the fundamental principles of backhand serve, recognize variations in short and long serve techniques, learn strategies for applying serves in game situations, and develop hand-eye coordination and stroke consistency. Through structured training with an interactive duel-based game approach, it is expected that students can improve backhand serve technique abilities, develop tactical decision-making skills, increase shuttlecock placement accuracy, and foster competitive spirit and sportsmanship in the school environment.